Effectiveness of the application of the endogenous-hypoxic breathing technique in the physical training of 13-16-year-old cyclists - Gavrylova, N.; Bohuslavska, V.; Pityn, M.; Moseichuk, Y.; Kyselytsia, O. (Journal of Physical Education and Sport, 2017)
The issue of perfection of functional and physical fitness of 13-16 year-old cyclists by means of application of the endogenous-hypoxic breathing techniques in the training process is investigated in the article. Due to the application of the endogenous-hypoxic breathing technique in combination with exercise loads, cyclists aged 13-16 years have positive changes in the apparatus of external respiration: the functional capabilities of the respiratory muscles are increased, the respiratory surface of the lungs increases, there is an economization of the respiratory muscles work in the relative muscular rest state, and it is also facilitated also passage of air in the area of medium and small bronchi is facilitated. The effectiveness of the complex application of normobaric hypoxia and hypercapnia, as well as the training loads on the physical fitness of adolescent cyclists, depends on the age of athletes. In the 13-14-year-old athletes, in 16 weeks after the beginning of the formative experiment, the special physical preparedness increased by the results of the cycling a 200 m flying-start heat (2.75 %, p <0.05) and the cycling a 2,000 m heat with a single turning (by 5.18 %, p <0.01); general physical fitness by results of running 60 m race (by 3,43 %, p <0,05), running a 1,500 m race (3,16 %, p <0,01) and the maximum number of squats in 15 sec (at 8, 57 %, p <0.005). In 15-16-year-old cyclists, training sessions with application of the endogenous-hypoxic breathing technique contributed to an increase in overall physical fitness - according to the results of running a 1,500 m race (2.29 %, p <0.02) and special physical fitness - according to the results of cycling a 2,000 m heat with one turn (5.91 %, p <0.005).